An Anthropology of Marxism - Robinson, Cedric J. (Book collections on Project MUSE., 2019)
This work presents Cedric Robinson's analysis of the history of communalism that has been claimed by Marx and Marxists. Accompanied by a new foreword by Helen Quan and a preface by Avery Gordon, this text reimagines the communal ideal from a broader perspective that transcends modernity, industrialization, and capitalism.